Antibacterial Activity, Antioxidant Benefits, Chemical Composition, and Physicochemical Properties of Ziziphus jujuba Honey from Five Distinct Regions in Morocco - Karima El-yagoubi; Mahmud Masalha; Basheer Abu-Farich; Soumaya Touzani; Badiaa Lyoussi; Bashar Saad (Journal of Pure and Applied Microbiology)
This study provides a comprehensive evaluation of Ziziphus jujuba honey, commonly referred to as sidr honey (SH), collected from five distinct botanical origins in Morocco: SHE from Errachidia (Daraa-Tafilalet), SHZ from Zaggota (Rabat-Sale-Kenitra), SHA from Ain Chair (Oriental), SHS from Saka (Oriental), and SHK from Khenifra (Beni Mellal-Khenifra). The research investigates the honey’s antibacterial properties against a range of gram-positive and gram-negative bacterial strains. Furthermore, key physicochemical parameters were analyzed according to international honey standards, including pH, electrical conductivity, Brix scale, refractive index, color, hydrosoluble protein, and total sugar content. Besides, bioactive compounds of SH honey samples, namely Total Flavonoid Content (TFC), and Total Phenolic Content (TPC) were measured. The antioxidant capacity was assessed through Total Antioxidant Capacity (TAC) measurements and the DPPH assay. The results demonstrated significant variations in the biochemical and physical properties of the SH samples. SHZ had the highest protein content at 209.59 ± 0.91 mg Eq BSA/100 g and TFC of 77.10 ± 1.21 mg QE/100 g, besides a strong antioxidant activity with a DPPH IC50 value of 10.53 ± 0.01 mg/ml and a TAC value of 50.23 ± 0.60 AAE/100 g. Antibacterial assays revealed that SHZ displayed the most potent antibacterial effects, particularly targeting gram-negative bacteria, with an MIC of 0.024 w/w% for S. aureus and 0.049 w/w% for P. aeruginosa, both with corresponding MBC values. In contrast, SHS demonstrated weaker antibacterial activity, with MIC values reaching 12.5 w/w% for several strains. In addition, the analysis of the honey samples indicates substantial relationships among physicochemical parameters, bioactive components, antioxidant and antibacterial activities. These results demonstrate that SH exhibits notable antibacterial and antioxidant properties, underscoring its potential as a natural health product. However, further studies are essential to explore the precise mechanisms driving these bioactive effects and their broader implications for health and nutrition.